Electronic Record Book Management System (E-Record Book) / Wong Kok Chung - Wong, Kok Chung (2003)
Electronic Record Book Management System (E-Record Book) is a client-server application that provides the headmaster and teachers with a more efficient and secure environment in managing and handling the electronic version of record books maintained by teachers. It is developed to support all operations on the manual record books used in schools nowadays. The objectives of E-Record Book are: 1. To provide teachers with ease of recording students' particulars, lesson plans and other related matters via an easy-to-use Web interface. 2. To provide the headmaster with a better monitoring and validation system on teachers' record books. 3. To create a better management environment by providing the headmaster and teachers with an online medium for effective communication and discussion. 4. To eliminate the unnecessary procedures in updating manual record books, and thus, reducing teachers' workload. 5. To enable teachers to update their own record book after working hours. 6. To provide a more secure way for the school administrator or school clerk to handle information on teachers and students. To provide such a good teaching and learning practices in schools, E-Record Book has been developed to provide 3 main sections : Administrator Section, Headmaster Section and Teachers Section. The Administrator Section allows the school administrator or clerks to create user accounts for teachers and the headmaster, informing any updates of events in the school and creating students' profiles and examination records. The Headmaster Section allows the headmaster to monitor the teachers' progress in teaching and to validate their lesson plans. Besides, the headmaster will also be able to post any comments on any written syllabus plan and/or lesson plans. In addition, the headmaster has the privilege to browse through any information on the teachers' profiles, timetable, syllabus plans, lesson plans and students' records. The Teacher Section allows teachers to manage their own E-Record Book as like the manual record book. They will be able to prepare their own timetable, syllabus plans, lesson plans, students' details and grades. Moreover, they will have the privilege to add or update the existing records and to check whether the headmaster has verified their record book. E-Record Book has been developed to help the headmaster and teachers to interact and deal with record books management more efficiently and effectively. This is also a way to promote a paperless environment, thus revolutionizing the way the record books are currently managed.